Environmentally benign nanomaterial synthesis mediated by culture broths - Liu, Lihong; Xie, F.; Meng, X.; Parek, V.; Liu, Shaomin (2017)
© 2017 Pan Stanford Publishing Pte. Ltd. Owing to their unique optical, electrical, chemical and physical properties, nanoscale materials have shown remarkable potential for widespread applications in electronics, catalysis, sensing and nanomedicine, among other fields (Kamyshny and Magdassi, 2014; Corain et al., 2008; Kumar et al., 2015; Etheridge et al., 2013). A multitude of protocols have been well established to synthesize nanoparticles (NPs), including chemical reduction (Flores et al., 2013), physical vapor deposition (Wang et al., 2007) and irradiation routes (Shin et al., 2004; Dhand et al., 2015). Unfortunately, conventional physicochemical methods result, in most cases, in high environmental and economic costs (Dahl et al., 2007). Hence, there is a significant benefit in developing 90nontoxic and environmentally benign biological processes for NP synthesis (Faramarzi and Sadighi, 2013).